The Constitutional Monarch and his Mini Zoo: The Case of Sultan Abdul Halim Mu’adzam Shah - Zamri, Zahid (Privacy Studies Journal, 2026)
Sultan Abdul Halim Mu’adzam Shah, the Sultan of Kedah in Malaysia who reigned between 1959 and 2017, was renowned for his great love for animals. Throughout his reign, he took care of a number of species of exotic and non-exotic animals as his pets in a private — yet semi-public — mini zoo that he built within the garden of his castle. This article explores the discussion of animal captivity ethics in Islamic thought, highlighting the role of the mini zoo within the Malaysian context. Moreover, this study attempts to understand how the privacy of these animals was leveraged by the Sultan to make them function as ‘mediators’ between him and his human subjects, which in turn explains the concept of privacy on his behalf. With data collected from official government publications, books, online national newspaper articles, and social media postings related to the Sultan and the mini zoo, this article argues that the privacy (or lack thereof) of the non-humans in the Sultan’s zoo reflects the Sultan’s own sense of privacy as the monarch.